A relação entre modernização neoliberal e práticas políticas atrasadas no Brasil dos anos 1990 - Lenardão, Elsio [UNESP] (FapUNIFESP (SciELO), 2008)
Our goal is to investigate the reasons behind the presence of clientelist-type practices among the popular classes in Brazil, highlighting the decade of the 1990s. Our proposal gives salience to factors regarding the phenomenon's socio-political conjuncture, thereby taking us beyond explanations that rely exclusively on historical-cultural aspects or that sustain an economic bias. We use bibliographic and journalistic sources, from which we develop our own interpretation of the period. Thus, we observe that clientelist practices are encouraged to manifest themselves at the level of national political organization particularly within the federal sphere yet are also reflected at state and municipal levels, due to the coalition of political forces created through the implantation of a neoliberal project in Brazil. The latter has joined modern Brazilian social democracy and old regional oligarchies situated primarily within the PFL, PP, PTB and certain sectors of the PMDB, whose representatives are known for their attachment to patrimonialist and paternalistic practices. The inclusion of the latter in the conservative pact that has promoted neo-liberal political reform has thus meant awarding new value to such practices. Herein lies partial explanation for the vigor with which practices such as fisiologismo, apadrinhamento, abuse of state machinery, buying and selling of votes and clientelism have manifested themselves on the national scene over the course of the 1990s.
The relationship between neo-liberal modernization and backward political practices in Brazil of the 1990s
Keywords: Brazilian politics; Conservative pact; Neo-liberal project; Political behavior; Political clientelism